The Relationship Between a History of Exclusive Breasfeeding and The Incidence of Diarrhea in Toddlers Aged 12-14 Months - Herlina Herlina; M Ridwan; Firda Fibrila; Lia Tri Wahyuni (Journal of Innovative and Creativity, 2025)
Diarrhoea remains a health problem and a leading cause of death among children in developing countries, including Indonesia, especially among children under five years of age. The prevalence of diarrhoea morbidity in Metro City in 2021 and 2022 was the same, reaching 21.84% among children under five years of age, and increased in 2023 to 24.6%. The Yosomulyo Community Health Centre had the highest prevalence of diarrhoea cases among children under five out of 11 community health centres in Metro City. The number reached 402 children under five (43.6%) out of 921 children under five who experienced diarrhoea cases in Metro City. One of the risk factors that can trigger diarrhoea cases is exclusive breastfeeding behaviour. This study aimed to determine the relationship between exclusive breastfeeding and the incidence of diarrhoea in children aged 12-24 months, using a cross-sectional design. The study population consisted of all children aged 12-24 months in the Yosomulyo Community Health Centre area. The sample was determined based on a proportion estimation formula, resulting in 93 children selected using a simple random technique. Interviews and medical record studies were the techniques used to collect data, utilising interview guides and observation sheets. Univariate and bivariate data analysis used the chi-square test. The results of the study on toddlers aged 12-24 months showed that 19% (19 toddlers) of those who were not exclusively breastfed experienced diarrhoea. The statistical test results showed a p-value of 0.000, indicating a relationship between exclusive breastfeeding and the incidence of diarrhoea in infants aged 12-24 months. Continuous education and counselling are needed from pregnancy to breastfeeding so that all infants receive exclusive breastfeeding and diarrhoea can be prevented.